CASE REPORT: POSTERIOR TIBIAL TENDON DISLOCATION - Trần Đức , Tài; Lê Trung, Hiếu; Bùi Thị, Hiền (Journal of 175 Practical Medicine and Pharmacy, 2023)
Posterior tibial tendon is a rare disease leading to misdiagnosis or delay. Most authors recommend that conservative treatment does not bring good results by surgery, therofore it is crucial to get the correct diagnosis early to make the appropriate treatment strategy. Exploiting medical history and clinical examination play a role as a guide to make appropriate image indications. We report the case of a patient who was diagnosed and had surgery early, initially giving good results.